Distances and Statistics of Local Molecular Clouds in the First Galactic Quadrant - Yan, Qing-Zeng; Yang, Ji; Su, Yang; Sun, Yan; Wang, Chen (The Astrophysical journal, 2020)
We present an analysis of local molecular clouds ( km s−1, i.e., <1.5 kpc) in the first Galactic quadrant ( and ), a pilot region of the Milky Way Imaging Scroll Painting (MWISP) CO survey. Using the Spectral Clustering for Interstellar Molecular Emission Segmentation algorithm to divide large molecular clouds into moderate-size ones, we determined distances to 28 molecular clouds with the background-eliminated extinction-parallax method using the Gaia DR2 parallax measurements aided by AG and AV; the distance ranges from 250 to about 1.5 kpc. These incomplete distance samples indicate a linear relationship between the distance and the radial velocity (VLSR) with a scatter of 0.16 kpc, and kinematic distances may be systematically larger for local molecular clouds. In order to investigate fundamental properties of molecular clouds, such as the total sample number, the line width, the brightness temperature, the physical area, and the mass, we decompose the spectral cube using the density-based spatial clustering of applications with noise (DBSCAN) algorithm. Post-selection criteria are imposed on DBSCAN clusters to remove the noise contamination, and we found that the separation of molecular cloud individuals is reliable based on a definition of independent consecutive structures in l-b-V space. The completeness of the local molecular cloud flux collected by the MWISP CO survey is about 80%. The physical area, A, shows a power-law distribution, dN/d , while the molecular cloud mass also follows a power-law distribution but is slightly flatter, dN/dM ∝ M−1.96 0.11.